The effects of antagonist prefatigue on agonist torque and electromyography - Maynard, J.; Ebben, W. P. (The Journal of Strength and Conditioning Research, 2003)
This study assessed the effects of hamstring prefatigue on peak torque, peak power, time to peak torque, knee angle of peak torque, and electromyography (EMG) activity of the hamstrings and quadriceps group during knee extensions at angular velocities of 60°, 180°, and 300°·s1. Twenty Division I wrestlers performed 5 maximal knee extensions in prefatigued and nonfatigued conditions of the hamstring group. This study demonstrated that when the hamstrings were prefatigued, the quadriceps produced significant decreases in peak torque of 1.7% (p < 0.05), peak power of 11% (p < 0.05), and rate to peak torque of 6.4% (p < 0.01) as compared with the nonfatigued state. When the hamstrings were prefatigued, they produced a 25% greater amount of EMG activity during knee extension (p < 0.01) than when not prefatigued. There was no significant difference in quadriceps EMG activity whether the hamstring group was prefatigued or not (p > 0.05). The decrease in quadriceps peak torque during the prefatigued condition was more pronounced (p < 0.01) at an angular velocity of 60°·s1 than at 180° or 300°·s1. In other words, prefatiguing the antagonist appears to be most detrimental to torque output of the quadriceps in the condition that most closely replicates the speed at which "isotonic" weight training occurs (60°·s1) and suggests a limitation to agonist-antagonist superset training.